PENGARUH TATA KELOLA PERUSAHAAN DAN AUDIT INTERNAL TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN JASA KONSTRUKSI - Galuh Ayu Putri (Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of corporate governance which includes audit committee independence, audit team competence, audit committee size, meeting intensity on the performance of construction service companies listed on the Indonesia Stock Exchange (IDX) with control variables of company size, liquidity, leverage, and tangibility. Sampling using purposive sampling technique with the criteria of companies listed on the IDX since before 2015. The data source is secondary data from the IDX. The data analysis technique used in this study used multiple linear regression analysis. The results of this study indicate that simultaneously all variables affect the company's performance. While partially the size of the company that has a significant effect on company performance.